Evaluación biométrico de un bosque primario, en el centro de producción e investigación Pabloyacu - Celiz Portilla, Mariela (2015)
The present thesis report was carried out in Pabloyacu research and production center during the months of January to August of 2013, has a database for the biometric evaluation of a primary forest, whose results can be used for future research projects as an adaptation to climate change, carbon sequestration, forest biodiversity, flora characterization of primary forest. The biometric evaluation of a primary forest of Pabloyacu Research and Production Center, its objectives in the research were: Determine the parameters of the biometric primary forest; apply the rectangular design in the inventory of biometric primary forest; and assess the value of the importance of a biometric primary forest. The results were that the biometric parameters made in the study area was able to obtain that: Found 14903 individuals shrubby; 717 individuals stem and that only 8% represents a range of 7.1 cm to 7.8 cm DAP, the maximum commercial height is 26.2 m and the maximum total height is 40.9 m in just a single individual (0.1 % ), the maximum volume of trade is > 0.1 m3 in three individuals (0.3 %) and the maximum total volume is > 0.1 m3 in nine individuals (1.3 % ). Found 470 tree individuals, only a individuals has the maximum range of 61.0 cm to 67.0 cm DBH, the maximum commercial height is 17.9 m in tour individuals (0.4 %), and the maximum total height is 31.8 m in 14 individuals, the maximum volume of trade is > 0.1 m3 in seven individuals (1.6 %) and the maximum total volume is > 2.0 m3 in four individuals (0.9 %). According to the biometric inventory within the rectangular design it was noted that there is a greater density of individuals that arable shrubby and its distribution is heterogeneous. The rectangular design according to the inventory biometric, it can be said of herbaceous plants, found 47727 individuals, the higher density is found in the triangle F (15608), which represents 32.7 %; the density of the entire area of research is of 4. 7 herbaceous/Ha. The shrubby plants of the highest density was found in the triangle E (6053 individuals), which represents 40.6 %; the density of the entire area of research is 1.5 shrubs/Ha. lts importance biometric herbaceous plants can be say, most of these were found in the triangles D and F, which represents an index of wealth of 25.1 %. Shrubby plant, the largest number of individuals were found in the triangles E and G, which represents an index of wealth of 25.1 %. Of the plants stem the largest number of individuals were found in the intervals 0,057 m to 0,071 m, which represents an index of wealth of 14.4 %, of the dominant plant, the largest number of individuals were found in the range 0,100 m to 0,214 m, which represents an index of wealth of 10.2 %. The findings suggest that the importance biometrics, is determined by the structure of the forest ecosystem, the individuals assessed are not forest production, but if environmental production, due to their dispersion and heterogeneous distribution and be treated by a primary forest, the environmental services offered are very important because they are directly related with four large areas of global concern: Climate change, biodiversity conservation, conservation of genetic resources and sustainable forest production. Key words: research projects, forest ecosystem.